Use of "Parasep filter fecal concentrator tubes" for the detection of intestinal parasites in stool samples under routine conditions - Mohammad Zeeshan; Afia Zafar; Zeb Saeed; Seema Irfan; Zain A Sobani; Sadia Shakoor; Mohammad Asim Beg (Wolters Kluwer Medknow Publications, 2011)
Parasitic gastrointestinal infections are a major cause of morbidity and mortality in the developing world, with stool microscopy being the mainstay of diagnostic practice. Both direct microscopy and concentration techniques can be utilized; direct microscopy may be time consuming and tedious; however clinical laboratories in developing countries lack trained staff who can effectively use concentration methods. In our practice we used the Parasep O and P filter concentrator tubes (manufactured by DiaSys Ltd, Berkshire, England. Product Code 146000) along with direct microscopic techniques and found that Parasep filters enhanced the ability to detect intestinal parasites that would have been missed on routine microscopy. We found the Parasep filter concentration method to be easy, cost-effective and reliable for routine stool examinations.